2012
DOI: 10.1016/j.jneumeth.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transcranial magnetic stimulation measures obtained at rest and under active conditions and their reliability

Abstract: 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
143
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(175 citation statements)
references
References 50 publications
(80 reference statements)
23
143
1
2
Order By: Relevance
“…Similar to other studies (Cacchio, Paoloni, 2011, Carroll, Riek, 2001, Ngomo, Leonard, 2012, Wheaton, Villagra, 2009, we found that active motor threshold demonstrated good reliability and was superior to the MEP size measures overall. This indicates that differences in threshold between sessions did not contribute substantially to the poor intersession reliability of MEP size in the stroke group.…”
Section: Reliability In Stroke and Control Groupssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to other studies (Cacchio, Paoloni, 2011, Carroll, Riek, 2001, Ngomo, Leonard, 2012, Wheaton, Villagra, 2009, we found that active motor threshold demonstrated good reliability and was superior to the MEP size measures overall. This indicates that differences in threshold between sessions did not contribute substantially to the poor intersession reliability of MEP size in the stroke group.…”
Section: Reliability In Stroke and Control Groupssupporting
confidence: 88%
“…Previous studies examining the reliability of MEPs have mainly focused on hand and forearm muscles (Bastani and Jaberzadeh, 2012, Carroll et al, 2001, Christie et al, 2007, Kamen, 2004, Livingston and Ingersoll, 2008, McDonnell et al, 2004, Mortifee et al, 1994, Ngomo et al, 2012, with a smaller number of studies examining muscles from the lower limb (Cacchio et al, 2009, Cacchio et al, 2011, Tallent et al, 2012, van Hedel et al, 2007, Wheaton et al, 2009). Most authors have reported good or excellent reliability of MEP amplitude measurements within and between sessions but this is not always consistent (Livingston andIngersoll, 2008, McDonnell, Ridding, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our inter-rater agreement for resting ppTMS measures was no better for ICF than SICI. Ngomo et al 9 observed that first dorsal interosseous SICI was reliable under resting but not active conditions. We observed both resting and active SICI measures were agreeable between sessions, though our agreement was greater for resting SICI.…”
Section: Discussionmentioning
confidence: 99%
“…How do these thresholds vary among individuals and situations? Some members of the MSD axis conduct research on neuromuscular mechanisms that may control the response to excessive exposure, focusing particularly on the biomechanical aspects of motor control (Côté et al, 2008;Fuller, Fung and Côté, 2011) and functional organization of the central nervous system (CNS) (Ngomo, Leonard and Mercier, 2012;Ngomo et al, 2011). For example, acute pain appears to stimulate complex adaptations such as increased movement variability, whereas chronic pain appears to limit variability (Côté and Hoeger Bement, 2010).…”
Section: Wmsd Exposure Measurement and Underlying Physiological Mechamentioning
confidence: 99%